A Case of Torsion in an Otherwise-Normal Ovary in a 22-years old nulliparous women: Utilization of Diagnostic Laparoscopy for the Accurate Diagnosis - Shetu, Shain Fariya; Begum, Kohinoor; Foysal, Mahamud Riyad (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Ovarian torsion can be seen in the otherwise-normal ovary and is a challenging issue in the emergency department. Definitive diagnosis is sometimes difficult to establish because of clinical symptoms similar to other abdominal diseases. We report a 22-year-old woman, nullipara, with acute lower right abdominal pain for 14 hours before coming to an emergency room. On examination, the abdomen was soft but tender over the right iliac fossa and rebound tenderness were present.Ultrasound radiological examination showed that the right ovary is grossly enlarged (volume- 98.4cc) with hyperechoic central stoma. On colour, doppler twisted pedicel was noted. Mild collection is also seen in the pouch of Doglus. During laparoscopy, we found a blackish-red cystic mass of about 12 × 11 cm experiencing torsion. Then salpingooophorectomy was done. This is an interesting case of torsion in an otherwise-normal ovary with a huge hematosalpinx. J Bangladesh Coll Phys Surg 2023; 41(4): 342-347